Multivariatne metode v varstvoslovju s programom SPSS - Erčulj, Vanja; Šifrer, Jerneja (2020)
Multivariate Methods in Criminal Justice and Security Using SPSS. The textbook covers the presentation of multivariate statistical methods, namely factor analysis, principal component analysis, discriminant analysis, clustering, multiple linear and logistic regression. It includes clear instructions and hands-on examples how to perform multivariate statistical analysis with statistical program SPSS.
Keywords: Multivariate statistical analysis; factor analysis; multiple regression; discriminant analysis; clustering; SPSS; program; validity of measurement; reliability of measurement